Mekanisme Pertahanan Diri sebagai Bentuk Defensi Tokoh Hasan dalam Naskah Drama Sarapan Terakhir Karya Andrian Eka Saputra - Nida Amalia Manggala; Rudi Adi Nugroho (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
The characters in every literary work have a conflict that makes the character experience anxiety and try to cover up his anxiety through self-defense. Self-defense mechanisms aim to protect a character or individual from external threats or impulses arising from internal anxiety. This form of self-defense is depicted through the character Hasan in the drama script